Results of concomitant groin-free percutaneous temporary RVAD support using a centrifugal pump with a double-lumen jugular venous cannula in LVAD patients - Schmack, Bastian; Farag, Mina; Kremer, Jamila; Grossekettler, Leonie; Brcic, Andreas; Raake, Philip; Kreußer, Michael; Goldwasser, Ranny; Karck, Matthias; Ruhparwar, Arjang (Journal of thoracic disease, 2019)
Background: Modern left ventricular assist devices (LVAD) have evolved to become standard of care in severe heart failure (HF) patients. Right HF (RHF) is a major complication responsible for early mortality. Several techniques for temporary right ventricular assist device (t-RVAD) have been described before, baring relevant disadvantages such as limited mobilization or the need for re-thoracotomy. We describe the results of an alternative technique for t-RVAD using the Tandem Heart™ with ProtekDuo™ cannula. - Methods: An institutional retrospective single centre outcome analysis was performed including all permanent LVAD recipients with concomitant groin-free t-RVAD support. - Results: Between October 2015 and September 2017, 11 patients (10 male, 90.9%) were included. Preoperative NYHA class was 3.8±0.75 and INTERMACS class 3.5±1.5. Four (36.4%) patients were already on mechanical circulatory support (MCS) at time of implantation with 4 (36.4%) patients already on inotropic support. All LVAD implantations were performed on-pump and 3 cases (27.3%) were re-do cases. Mean t-RVAD duration was 16.8±9.5 days. Ten patients (90.9%) could be weaned from temporary RVAD support, 1 patient deceased on support. Mean ICU stay was 23.8±16.5 days, while 30-day survival was 72.7%. Follow-up was complete with 214.7±283 days. Three patients (27.3%) died following multi-organ failure (MOF), 1 patient (9.1%) following intracranial bleed 12 days after t-RVAD explantation. No severe t-RVAD associated complications were observed. - Conclusions: Our technique allows for safe groin-free t-RVAD providing all advantages of percutaneous implantation including complete mobilization and bedside explantation without any need for operation.
Gesehen am 23.07.2019